AN EXAMINATION OF SPORT MENTAL TOUGHNESS AMONG INTERNATIONAL AND HUNGARIAN BASKETBALL PLAYERS - Németh, Kata; Rátgéber, László; Bács, Zalán; Balogh, László (Stadium - Hungarian Journal of Sport Sciences, 2025)
In our research, we compared the mental results of Hungarian basketball players to international averages. We examined the degree of mental toughness of the athletes who filled out the SMTQ questionnaire, whether they are motivated to achieve success, and whether they maintain their self-confidence (even despite occasional failures). Our goal was to indicate Hungarian athletes’ mental strengths and weaknesses, thus helping the athletes’ preparation. The aggregate mental toughness scores indicated that Hungarian basketball players are above the international average. Still, in terms of control, it is below average in certain age groups. The adult age group (over 18 years of age) is recommended to develop autonomy and responsibility and maintain self-control. It is necessary to improve the influence of their behavior, emotions, and self-regulation. Confidence scores assume that respondents believe in themselves and their successes. They have a positive attitude and a failure-averse attitude. Endurance results will likely be goal-oriented athletes who do not give up and can maintain their motivation.